Promosi Kesehatan Reproduksi Melalui Pencegahan Perilaku Seksual Berisiko pada Remaja - Yulia, Yulia; Rahma, Gusni; Rizyana, Nurul Prihastita; Camellia, Artha (Jurnal Pengabdian Ilmu Kesehatan (JPIK), 2024)
Based on the results of previous research on the determinants of risky sexual behavior in high school level teenagers in Padang City, it was found that 42.7% of high school level teenagers had a history of risky sexual behavior where the dominant factor influencing this risky sexual behavior was the knowledge factor with value. PR 2.86. Therefore, it is necessary to carry out community service activities to increase teenagers' knowledge about reproductive health so that they can control and prevent risky sexual behavior. The aim of implementing this health promotion is to provide promotion about reproductive health to prevent risky behavior in adolescents. The activity was conducted at School X in Padang with 50 participants. The activity method is carried out through counseling and group discussions. This community service activity is carried out based on three stages: preparation, implementation, and evaluation. Based on the results of activity evaluations carried out using pre-tests and post-tests, it was found that there was an increase in the proportion of good knowledge among activity participants from 50% to 80% after being given promotions about reproductive health. Meanwhile, participants' positive attitudes increased from 50% to 74% after being given health promotion.